The Arabidopsis Mitogen-Activated Protein Kinase Kinase Kinase 20 (MKKK20) Acts Upstream of MKK3 and MPK18 in Two Separate Signaling Pathways Involved in Root Microtubule Functions - Benhamman, Rachid; Bai, Fangwen; Drory, Samuel B.; Loubert-Hudon, Audrey; Ellis, Brian; Matton, Daniel P. (Frontiers in Plant Science, 2017)
Mitogen-activated protein kinase (MAPK) signaling networks represent important means of signal transduction in plants and other eukaryotes, controlling intracellular signaling by linking perception of environmental or developmental cues to downstream targets. In the Arabidopsis MEKK subfamily, the MKKK19, 20 and 21 form a highly supported clade with the Solanaceous Fertilization-Related Kinases. In Arabidopsis, little is known about this group, except for MKKK20, which is involved in osmotic stress. Using a directed MKKK-MKK yeast two-hybrid (Y2H) screen, MKKK20 was found to interact only with MKK3, while a MKKK20 large-scale Y2H screen retrieved MPK18 as a direct interactant. In vitro phosphorylation assays showed that MKKK20 phosphorylates both MKK3 and MPK18. However, when all three kinases are combined, no synergistic effect is observed on MPK18 phosphorylation, suggesting a direct access to MPK18, consistent with the absence of interaction between MKK3 and MPK18 in protein-protein interaction assays. Since mpk18 mutant plants were previously shown to be defective in microtubule-related functions, phenotypes of mkkk20 single and mkkk20/mpk18 double mutants were investigated to determine if MKKK20 acts upstream of MPK18. This was the case, as mkkk20 root length was shorter than WT in media containing microtubule-disrupting drugs as previously observed for mpk18 plants. Surprisingly, mkk3 plants were also similarly affected, suggesting the presence of two non-complementary pathways involved in Arabidopsis cortical microtubule function, the first including MKKK20, MKK3 and an unknown MPK; the second, a non-canonical MAPK cascade made of MKKK20 and MPK18 that bypasses the need for an MKK intermediate.